Endovascular Stent Graft Exclusion of an Iatrogenic Tracheoinnominate Fistula after Unsuccessful Surgical Repair - Woerner, Andrew; Koo, Kevin S. H.; Monroe, Eric J. (Journal of Clinical Interventional Radiology ISVIR, 2018)
A 10-year-old girl with metachromatic leukodystrophy developed a tracheoinnominate artery fistula and massive hemoptysis following tracheostomy, initially requiring open surgical repair. Massive hemoptysis recurred at 1 month due to suspected pericardial patch dehiscence. The authors herein describe the subsequent emergent treatment by stent graft exclusion and review the existing literature surrounding this rare and potentially fatal condition.
Keywords: pseudoaneurysm; innominate artery; stent